Evaluasi Dampak Kebijakan Penyelenggaraan Pelayanan Terpadu Satu Pintu di Badan Pelayanan Perizinan Terpadu Kota Semarang - Tahalea, Stephani Nora; Suwitri, Sri; Rostyaningsih, Dewi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
In this kind of era that full of challenges and chances, Local Government should be able to do some innovation to improve the quality of public services, so that the impression of government bureaucracy that is slow, complicated, and unfriendly can be eliminated. Therefore a policy was made to solve the problems that are exist in the public. The Implementation of One Stop Services have done to overcome the problems, especially in the licensing and non-licensing areas. The purpose of this policy is to facilitate the public in the making of business license. This policy was expected to have an impact to society beyond the aim of this policy itself. The purpose of this study was to find out what the impact of PPTSP, both expected and unexpected aspects of individuals, organizations, institutions and social systems. This research is a descriptive study using a qualitative approach. Based on result of research, PPTSP policy was still not touched all aspects of the society in which people are still not fully feel the positive impact of this policy. The recommendations that can be given to BPPT is this implementation of PPTSP can pay more attention to the impact resulting from the ease of licensing is not only for entrepreneurs, but also for the people are not entrepreneurs. The coordination of BPPT and related agencies should be improved, and in the policy making stakeholders must take an anticipatory action to tide over the impacts that are out of the expectation.